Parameters in Canines After Cesarean Sections - Theresa Conze; Kathrin Büttner; Axel Wehrend (Frontiers in Veterinary Science, 2022)
This study evaluated fertility in canines after cesarean section and compared it with natural parturition. Parameters, such as the time of the next heat after the first parturition or cesarean section, the heat which was used for another breeding attempt, whether it was successful, the number of puppies that were born, and the necessity of another cesarean section were examined. The study relied on questioning patient owners at a University clinic. A Google online form was also used. Information for 261 dogs from different breed groups was included, of which 119 bitches were in the cesarean section group, and 142 were in the natural parturition group. In total, 93 ± 2.7% [LSMeans ± standard error (SE)] and 91.12 ± 3% (LSMeans ± SE) of the bitches became pregnant after cesarean section and natural parturition at the first breeding attempt. There was no significant effect on the breed group or whether the bitch had undergone a cesarean section before (p = 0.8 and p = 0.63). Bitches, which underwent a cesarean section, were more likely to have further cesarean sections performed (p < 0.001). However, neither the breed groups (p = 0.17), whether the bitch had undergone a cesarean section (p = 0.59), nor the number of previous parities had any effect on the number of puppies born (p = 0.95). The breed group bulldogs had a high proportion of cesarean sections. Only 42.11% of the bulldogs had a natural parturition as the first included parturition and only 31% gave birth naturally thereafter.